Development of a Photoresponsive and Electrostrictive Material from P(VDF-TrFE-CFE) and TiOPc Composite. Issue 1659 (14th January 2014) - Chang, Wen-Chi; Chen, Po-Han; Lin, Chih-Ting; Wang, An-Bang; Lee, Chih-Kung
ABSTRACT: Optical control is a reversible and convenient technology, able to be measured in real-time, which makes it excellent for application to microfluidic, biomechanical, and electro-mechanical devices. These advantages are especially attractive for photo-responsive materials. In this study, we developed a new photo-responsive, electrostrictive material from a composite material made by mixing a dielectric polymer P(VDF-TrFE-CFE) and an organic photoconductive material TiOPc. The photo-responsibility of the material has been validated by corresponding actuators. We found that under white light illumination, deformation will increase which can be attributed to a decrease in the TiOPc impedance. We identified that the optimal TiOPc concentration for actuator applications is 10% P(VDF-TrFE-CFE)/TiOPc. Moreover, controlling the fluid flow within the capillary tube through light illumination also validated the photo-responsive actuator. Our results show that the mechanism and the photo-responsive material can be used to pursue further study on light controlling microfluidic, and related electro-mechanical devices.